Performance optimization of a thermoelectric energy harvesting system utilizing waste heat from an internal combustion engine - Gbaarabe, Baribuma; Sodiki, John I.; Lebele-Alawa, Barinaadaa Thaddeus; Nkoi, Barinyima (Applied Engineering and Technology, 2025)
This study presents the performance optimization of a Thermoelectric Energy Harvesting (TEH) system designed to recover waste heat from Internal Combustion Engines (ICEs). It includes optimizing the energy conversion efficiency of the thermoelectric module (TEM), optimizing the design of the Plate Heat Exhcanger (PHE), and simulation-based validation. The optimization process, conducted using Python optimization code developed for the study, yielded an energy conversion efficiency of 7.209%, marking a 56% improvement over the experimentally measured efficiency of 4.63%. The optimized PHE design, incorporate finless triangular-rectangular composite duct. The analysis showed a fully turbulent flow within the PHE, which significantly enhances convective heat transfer coefficients, improve the  heat exchange between the exhaust gas and heat exchanger surfaces, and reduces the risk of fouling and clogging. The exhaust gas contained 1792W of waste heat, with 230W transferred to the hot side of the TEM. This corresponds to a heat exchanger effectiveness of 0.13, indicating that only 13% of the available waste heat in the exhaust gas is utilized by the TEM. The overall TEH system efficiency was determined to be 0.94%, which, despite being relatively modest, yields considerable energy savings in large-scale applications where waste heat is abundant. Computational simulations, using a CAD model in SOLIDWORKS, validated the TEH system’s optimized performance, by ensuring the desired temperature gradient is maintained across the TEM, given that the power output of the TEH is directly proportional to the temperature gradient across the thermoelectric couples in the TEM